IMPLEMENTASI MINDFULNESS LEARNING DALAM MENINGKATKAN KEMAMPUAN PEMECAHAN MASALAH PADA PERKALIAN DAN PEMBAGIAN PECAHAN DI MTS NEGERI PAREPARE - Nurjannah; Nurwahida; Buhaerah; Azmidar (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to describe the implementation steps of Mindfulness Learning and analyze its effectiveness in improving students’ mathematical problem-solving skills on the topic of fraction multiplication and division at MTs Negeri Parepare. The low level of problem-solving ability was identified as being caused by a lack of focus, attention, and mental engagement during learning activities. This research employed a quantitative approach with a quasi-experimental design (one-group pretest–posttest). Data were collected through observation, mathematical problem-solving tests, and documentation, then analyzed using descriptive and inferential statistics with a paired sample t-test. The results are expected to show a significant improvement in students’ mathematical problem-solving abilities after the implementation of Mindfulness Learning, as well as positive behavioral changes toward more focused, calm, and reflective learning habits.